2020
DOI: 10.1186/s41241-020-00094-x
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-methods evaluation of a group based trail walking program to reduce anxiety in cancer survivors

Abstract: Background Cancer survivorship results in an increased number of physical and psychosocial health issues. Engaging in physical activity in natural environments is often thought of as restorative. Despite the potential benefits of engaging in physical activity in natural environments there are no sustainable community-based programs for cancer survivors that employ this form of physical activity. This study aims to evaluate the impact of an 8-week trail-walking (TW) program on anxiety in a population of adult c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Similarly, we found that cancer survivors who participated in more outdoor physical activity reported greater physical activity enjoyment and benefit. We also found that a significant reduction in perceived stress in cancer survivors who participated in a bi-weekly 8-week trail walking program and a significant reduction in state anxiety after each trail walk [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, we found that cancer survivors who participated in more outdoor physical activity reported greater physical activity enjoyment and benefit. We also found that a significant reduction in perceived stress in cancer survivors who participated in a bi-weekly 8-week trail walking program and a significant reduction in state anxiety after each trail walk [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review, half of the reviewed studies found a significant relationship between social support and physical activity engagement in cancer survivors [ 1 ]. We also found this in our trail walking program for cancer survivors where social support was stated as highly important and ensured accountability especially in an outdoor setting with potential for adverse weather conditions [ 17 ]. However, it is important to note that there was also concern over a group environment, with group physical activity being a potential barrier if there were poor group dynamics or scheduling of activity was prohibitive to engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we systematically reviewed the literature for evidence of the effect of nature walks on anxiety and depression outcomes. Nature walks are walks on a trail in a natural setting such as forests, woodlands, or parks [30] that can take any time from 15 min [31] to a few hours [32]. Nature walks can be undertaken by diverse populations (e.g., cancer survivors [32], university students [33]) and conducted in any season of the year [31,34].…”
Section: Introductionmentioning
confidence: 99%
“…Among the longitudinal, the association was more inconsistent; three found an association while two did not. The two studies that did not find an association focused on notions of well-being [39,45], whereas the three that did, focused on enjoyment, quality of life, and mindfulness [38,43,56].…”
Section: Relationship Between Long-distance Walking and Mental Healthmentioning
confidence: 96%
“…The only study that did not find a positive effect found that long-distance walking did not have a negative effect [40]. One study [39] examined both measures of emotional distress and well-being and found that long-distance walking was not related to wellbeing but was related to a significant reduction in some measures of emotional distress. This, however, depended on the measure of emotional distress, finding non-significant reductions in depression and generalized anxiety, but significant reductions with regards to stress and state anxiety.…”
Section: Relationship Between Long-distance Walking and Mental Healthmentioning
confidence: 99%